Discovery of the pan-genotypic hepatitis C virus NS3/4A protease inhibitor voxilaprevir (GS-9857): A component of Vosevi®. Issue 16 (15th August 2019) - Taylor, James G.; Zipfel, Sheila; Ramey, Kyla; Vivian, Randy; Schrier, Adam; Karki, Kapil K.; Katana, Ashley; Kato, Darryl; Kobayashi, Tetsuya; Martinez, Ruben; Sangi, Michael; Siegel, Dustin; et al.
Graphical abstract: Abstract: Treatment of hepatitis C virus (HCV) infection has been historically challenging due the high viral genetic complexity wherein there are eight distinct genotypes and at least 86 viral subtypes. While HCV NS3/4A protease inhibitors are an established treatment option for genotype 1 infection, limited coverage of genotypes 2 and/or 3 combined with serum alanine transaminase (ALT) elevations for some compounds has limited the broad utility of this therapeutic class. Our discovery efforts were focused on identifying an NS3/4A protease inhibitor with pan-genotypic antiviral activity, improved coverage of resistance associated substitutions, and a decreased risk of hepatotoxicity. Towards this goal, distinct interactions with the conserved catalytic triad of the NS3/4A protease were identified that improved genotype 3 antiviral activity. We further discovered that protein adduct formation strongly correlated with clinical ALT elevation for this therapeutic class. Improving metabolic stability and decreasing protein adduct formation through structural modifications ultimately resulted in voxilaprevir. Voxilaprevir, in combination with sofosbuvir and velpatasvir, has demonstrated pan-genotypic antiviral clinical activity. Furthermore, hepatotoxicity was not observed in Phase 3 clinical trials with voxilaprevir, consistent with our design strategy. Vosevi ® (sofosbuvir, velpatasvir, and voxilaprevir) is now an approved pan-genotypic treatment option for the most difficult-to-cure individuals who have previously failed direct acting antiviral therapy.